The Mask of Leadership: Reflection on Art-Based Learning for Preservice Teachers - Zuhkhriyan Zakaria; Arief Ardiansyah; Wathanan Srinin; Citra Kurniawan; Robby Hidajat (Journal of Leadership in Organizations, 2023)
Introduction/Main Objectives: Leadership and educators face numerous personal and professional challenges. The challenge for prospective teachers is to prepare themselves to be leaders in the classroom, but they still do not understand the true meaning of reflecting leadership. Background Problems: How do teacher candidates reflect on leadership? Novelty: This study seeks to find new ways to increase their understanding of their leadership. This hands-on learning approach is based on an online masking workshop that examines leadership styles and behaviors, reflection, and hidden agendas. Nineteen prospective elementary school teachers from Indonesia participated in the study. Research Methods: This study argues that this is a research descriptive qualitative study in which the researcher uses a mask maker to capture the expressions of prospective elementary school teachers. Finding/Results: The results of the workshops are fun and exciting. These activities encourage creative and lateral thinking, foster self-awareness, and can provide access to information beyond the goal through the expressive metaphor of the mask. Visual, emotional, and aesthetic development, when combined with non-directive professional dialogue, can result in more effective, authentic, and thus ethical and dynamic leadership. Conclusion: Participants indicated that exploring experiences through art-based methods is a rewarding process, as is creating work, taking a logical approach to reflective practice, and engaging in fruitful self-exploration.